OUTDOOR SURVIVAL SKILLS - Olsen, Larry Dean (Chicago Review Press, 2021)
Outdoor Survival Skills has taught generations of wilderness adventurers how to survive in nature without expensive purchased equipment, instead drawing on knowledge of the land and carefully tested techniques, many of them ancient, for finding or creating shelter, fire, tools, water, and plant and animal foods